2022
DOI: 10.1039/d1en01068a
|View full text |Cite
|
Sign up to set email alerts
|

Bioreactivity of a novel poly(epsilon-caprolactone) nanocapsule containing atrazine with human lung alveolar epithelial cells

Abstract: Nanoencapsulation of pesticide atrazine improves efficacy. However, this study discovered adverse bioreactivity in alveolar type 1 epithelial cells (a major recipient of inhaled nano-sized particles), following exposure to nanoencapsulated atrazine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 81 publications
(134 reference statements)
0
2
0
Order By: Relevance
“…Considering the fact that atrazine is harmful to humans and animals, Moore et al [107] prepared nano-PCL-atrazine and evaluated its effect on human lung cells, as atrazine may reach respiratory units via inhalation. In previous research, it was reported that nano-PCL-atrazine was safer to human cells than atrazine, but, according to the results of this investigation, 48 h after the exposure of cells to nano-PCL-atrazine with concentrations of more than 1 ppm, the dehydrogenase release of lactate notably increased, with a maximum at 5 ppm, which was three times more than the control cells.…”
Section: Atrazine-pcl Nanoherbicidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the fact that atrazine is harmful to humans and animals, Moore et al [107] prepared nano-PCL-atrazine and evaluated its effect on human lung cells, as atrazine may reach respiratory units via inhalation. In previous research, it was reported that nano-PCL-atrazine was safer to human cells than atrazine, but, according to the results of this investigation, 48 h after the exposure of cells to nano-PCL-atrazine with concentrations of more than 1 ppm, the dehydrogenase release of lactate notably increased, with a maximum at 5 ppm, which was three times more than the control cells.…”
Section: Atrazine-pcl Nanoherbicidesmentioning
confidence: 99%
“…Such effects were not observed in cells treated with atrazine or PCL nanocapsules. Therefore, nano-PCL-atrazine caused more damage to human lung alveolar cells than atrazine or PCL nanocapsules; however, nanoformulations provide higher herbicidal activity and can be applied at lower dosages, thus causing less ecological contamination [107].…”
Section: Atrazine-pcl Nanoherbicidesmentioning
confidence: 99%